Ewolucja przepisów regulujących proces inwestycyjno-budowlany w zakresie infrastruktury telekomunikacyjnej - Prusik-Serbinowski, Filip (PRAWO i WIĘŹ, 2025)
The purpose of this paper is to present the evolution of the regulations governing construction investments in telecommunications infrastructure against the background of its growing socio-economic importance. In light of these changes, the legislator, wishing to facilitate construction investments in this area, has consistently liberalised the regulations governing the conduct of such investments. However, telecommunications infrastructure consists of technically complex structures, and their implementation is not indifferent when it comes to environmental protection, spatial order, or the rights and interests of neighbouring property owners. Thus, there is a conflict of values that the legislator has to resolve and which affects the interpretation and application of the law. As a result, telecommunications infrastructure is treated specifically in many areas of administrative law, including dedicated exemptions from a number of obligations. An important element of the paper will be the analysis of the case law of administrative courts against the background of changing regulations. This is because legislative changes introduced to facilitate the investment process in telecommunications infrastructure are often interpreted narrowly by the courts. It can be said that the administrative courts go a bit against the legislator, perhaps wanting to protect spatial order, the environment or individual rights. References to the legislative process and legislative materials are an important part of the analysis.